The Use of Public Support Mechanisms by Tourism Enterprises on the Border Between Poland and Czechia – A Comparative Analysis - Zawadzki, Piotr (Publishing House of Wroclaw University of Economics and Business, 2025)
The COVID-19 pandemic posed a significant challenge to the modern world, exerting multifaceted impacts on the functioning of socio-economic structures. Under crisis conditions the risk of economic destabilisation emerged, leading to new challenges and the necessity to implement public support mechanisms. This article focuses on analysing measures introduced to mitigate the effects of the pandemic and related crises in the tourism sector. The author compared public support mechanisms, their forms of utilisation, and the financial situation assessment of SMEs operating in the tourism industry along the Polish-Czech border. The research findings indicate that, despite geographical proximity, enterprises differed in terms of the types of support used, the barriers encountered in accessing it, and their subjective assessments of current and future financial conditions.
Quote as: Zawadzki, P. (2025). The Use of Public Support Mechanisms by Tourism Enterprises on the Border Between Poland and Czechia – A Comparative Analysis. In B. Drelich-Skulska, M. Sobocińska, & A. Tomášková (Eds.), Sustainable Development in Light of Research by Scientists from Poland, Czechia and Slovakia. Different Research Perspectives (pp. 135-147). Publishing House of Wroclaw University of Economics and Business.
Keywords: COVID-19 pandemic; public support; tourism enterprise